Pseudomonas aeruginosa resistente aos carbapenêmicos em um hospital universitário de referência: impacto clínico, resistência e virulência - Cunha, Jane Eire Urzedo (2020)
Introduction: Pseudomonas aeruginosa is frequently involved with healthcare-related infections (HAIs) in Brazil, high mortality rates and has a great capacity to develop or acquire resistance to antimicrobials. Objectives: This study investigated the impact of inappropriate antimicrobial therapy on the evolution of patients with carbapenem-resistant P. aeruginosa infection and its association with genes responsible for encoding metallo-β-lactamases (blaIMP, blaVIM, blaSIM, blaGIM, blaSPM, blaNDM) and exotoxins of the Type III Secretion System (T3SS III) - exoS, exoT, exoU and exoY. Material and methods: A retrospective cohort was performed to determine risk factors for mortality within 30 days and the impact of inappropriate empirical therapy on patients with a first infectious episode due to P. aeruginosa (262 patients). The blaIMP, blaVIM, blaSIM, blaGIM and blaSPM genes, the T3SS genes (exoT, exoS, exoY, exoU) were detected by PCR. Results: The results obtained were frightening when it comes to the mortality rate. It was observed that 17.9% of patients with infection died within 5 days of diagnosis and the rate of inappropriate empirical therapy was 52.7% and was associated with a worse prognosis. Most of the patients included in the study had multidrug-resistant P. aeruginosa infection (59.5%). Also, patients with comorbidities who developed P. aeruginosa infections were more likely to receive inappropriate empirical therapy and the mortality rate was significantly higher in this group (75.5%). In addition to inappropriate empirical therapy, prolonged hospital stays; the presence of comorbidities such as neoplasia, nephropathy and heart disease; the use of invasive devices, were independent factors for early mortality. The results are even more significant considering that 64.5% of the isolates had a T3SS gene, exoT being the most common gene. Although the exoU gene was found in less than 20% of the isolates evaluated, this genotype was significantly more frequent among multiresistant samples (80%) and associated with a worse prognosis in 46.7% of cases. Conclusions: These results demonstrate that P. aeruginosa remains one of the most important pathogens in the hospital environment, affecting mostly critical patients. Here, we realize that inappropriate antimicrobial therapy is closely related to the worst prognosis for patients, especially those with more serious infections such as bacteremia and pneumonia. Our results also suggest that multi resistance associated with virulence (T3SS) should be added to the list of factors responsible for increased mortality rates in these patients. Regardless of the low detection of genes associated with resistance to carbapenems in our cohort, the importance of combining mechanisms that lead to resistance must be considered and studied. This study becomes essential so that, shortly, new strategies can be formulated and implemented to decrease the rate of infection by multidrug-resistant P. aeruginosa, the prescription of inappropriate empirical therapy and, consequently, significantly reduce the rates of mortality.